The Effectiveness of Macroeconomic Commitment in Weak(er) Institutional Environments - Quintyn, Marc (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes the institutional conditions affecting the establishment and effectiveness of independent central banks and of budgetary institutions. It draws on the recent theory developed by North, Wallis and Weingast on the transition from a closed and fragile state to an open economic and political environment. The paper presents a composite indicator allowing for the identification of a country's position along this transition path. The findings suggest that (i) while the establishment of autonomous central banks seems to be relatively independent from the broader institutional framework, sound budgetary institutions tend to be established in countries with higher levels of rule of law for the elites, and (ii) while central bank independence is effective in reducing inflation irrespective of a country's position along the transition path, budget institutions seem to be most effective as a disciplining device in weak institutional environments.